Short Communication Investigation of Starch Modification Potential of ‘Kanwa’ – an Alkaline Salt: Short Communication: Starch Modification Potential of ‘Kanwa’ (Biological Sciences - PJSIR, 2009)
Cassava-starch-modification potential of ‘Kanwa’ at different concentrations was studied. Kanwa modified cassava-starches showed better swelling power, paste clarity, viscosity, peak viscosity, freeze-thaw stability and reduced gelatinization time over native starch. However, native starch had better water solubility and set back viscosity.